Arsenic mobilization processes in the red river delta, Vietnam : towards a better understanding of the patchy distribution of dissolved arsenic in alluvial deposits - Eiche, Elisabeth (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Mineralogie und Geochemie, 2009)
The spatial variability of dissolved arsenic (As) concentrations in aquifers was studied near Ha Noi, Vietnam. The goal was to identify major geochemical, sedimentological and hydrochemical differences between high and low As regions. Also, the behaviour of As and other elements during sequential extractions was characterized with micro synchrotron XRF analysis. Based on the results a conceptual model was developed which could explain the current situation on site and in other affected areas.